STUDI SIFAT FISIK BIJI KECAPI (Sandoricum koetjape Burm. f. Merr) DAN PENYIMPANANNYA DALAM SUHU KAMAR - Aprilianti, Popi; Putri, Winda Utami (Buletin Kebun Raya, 2009)
The Santol fruit (Sandoricum koetjape Burm. f. Merr.) is one of the most important fruit trees in Meliaceae. It possesses seeds with sticky white aril that cannot be stored for a long term because of its characteristic as recalcitrant seeds. The aim of this research was to study the storage period of the santol seeds in the room temperature. Measurements were conducted on seed characteristics such as weight, length, seed thickness, water content, seed viability, and germination rate. The result shows that santol seed can be stored maximum for 40 days. Between 30-40 days the seed can still germinate but the seedling is in normal strong and normal weak category. Based on water content measurement and viability observation, santol seed can be grouped as recalcitrant.